Obesitas dan Obesitas Sentral pada Masyarakat Usia Dewasa di Daerah Perkotaan Indonesia - Septiyanti Septiyanti; Seniwati Seniwati (Jurnal Ilmiah Kesehatan (JIKA), 2020)
Obesity is a problem in various parts of the world where its prevalence is increasing rapidly, both in developed and developing countries Obesity can occur because of an imbalance between the energy from the food that comes in, which is greater than the energy used by the body. This study aimed to see the characteristics of obesity and central obesity in adult society in urban areas of Indonesia. This study used a cross-sectional study, by analyzing advanced data on Basic Health Research (Riskesdas) in the biomedical field. The results of this study indicated that in general obesity and central obesity increase with age, with the highest prevalence being at the age of 40-59 years. Both obesity and central obesity were more prevalent in female subjects. Obesity and central obesity were also more common among subjects who graduated from high school and who work as housewives. Subjects of obesity and central obesity experienced more abnormalities in biomedical examination than those with normal BMI and abdominal circumference. For this reason, it is advisable to maintain a normal BMI and abdominal circumference, especially for adults. This study proves that there are significant differences in biomedical examination in those who are obese and not obese.